The Effect Follicular Fluid Vitamin A, E, D and B6 on Embryo Morphokinetics and Pregnancy Rates in Patients Receiving Assisted Reproduction - Gode, Funda; Akarsu, Suleyman; Dikmen, Zeliha Gunnur; Tamer, Burcu; Isik, Ahmet Zeki (Gynecology Obstetrics & Reproductive Medicine, 2019)
Objective: To evaluate the associations among levels of vitamins A, E, D, and B6 in follicular fluid embryo morphokinetics and quality, and clinical pregnancy rates. Study Design: A total of 58 patients with unexplained infertility admitted to the in vitro fertilisation (IVF) centre of Izmir Medical Park Hospital were included in this prospective clinical study. For each patient, vitamin levels were assayed using high-performance liquid chromatography. After intracytoplasmic sperm injection, for each oocyte, the relationships between each vitamin and subsequent embryo quality, embryo morphokinetics, and clinical pregnancy rates were investigated. Embryos were classified as grade A, B, C, or D according to morphokinetic parameters using t5-t2 and t5-t3 (cc3). Results: There was no significant correlation between embryo morphokinetic parameters (tpnf, t2, t3, t4, t5, t6, t7 and t8) and follicular fluid vitamin (A, B6, D and E) levels (p>0.05). There was a significant positive correlation between t5optimal and follicular fluid vitamin A levels (p<0.05). There was a significant positive correlation between cc2optimal and follicular fluid vitamin B6 levels (p<0.05). Levels of vitamins A and B6 were significantly higher in grade A and B embryos than in grade C and D embryos. There were no significant relationships between vitamins E or D and embryo quality or between any vitamin and clinical pregnancy rates. Conclusion: High levels of vitamins A and B6 in follicular fluid are significantly associated with high-quality embryos and optimal morphokinetics. However, none of the vitamins considered showed a significant relationship with clinical pregnancy rates.